Doctor Reisa's role as A Brand Ambassador for Dettol - Azzahra, Farah Putri; Barkah, Cecep Safaatul; Chan, Arianis; Tresna, Pratami Wulan (The International Journal of Business Review (The Jobs Review), 2021)
Abstract. This journal measure effectiveness Doctor Reisa’s role as Brand Ambassador for Dettol. Measurement is done with survey to consumer based on consumer behavior and also based on theory of Brand Ambassador. This research created several conclusion based on analysis to consumer of Dettol. The object of this research is Dettol, a brand name which is an antiseptic liquid disinfectant manufactured by Reckitt Benckiser, one of the most popular healthcare products in the world and Doctor Reisa, an Indonesian doctor, actress, model, and presenter, also Head of Communications for the Task Force for the Acceleration of Handling COVID-19 in Indonesia. Doctor Reisa represent a work-mom with child and a credivility source. The measurement results can be consideration for choosing the right Brand Ambassador.Keyword. brand ambassador; dettol; credibility source